Rodeo as a sport practice of cultural identity in in the southern region‬ of Brazil - Kirinus, Jackeline; Simon, Veridiana; Zago, Letícia; Magalhães, Danielle Rodrigues; Levrino, Gustavo A. María; Sañudo Astiz, Carlos Sañudo Astiz (Pubvet, 2018)
The interaction activities between man and animal that are seen as a sport began with the practices of the rodeo throughout history. From this, these practices became cultural events, such as: festive character, thanksgiving, entertainment and especially conventions related to livestock. This study aims to verify the opinion of the population of Southern Brazil, for the use of animals in sports practices during the course of rodeos or similar events, the main point of discussion is the animal welfare. For data collection an online questionnaire (Google Docs Software) was applied by sending e-mail or through collections in classrooms. It was composed by 16 questions that were objective and related to the subject of rodeos and /or similar events. They were divided into sections: lovers/supporters, art/culture/identity, socioeconomic, emotional impact (sensations) and animal welfare. Thus, from the total respondents (n = 504) it was concluded that the majority of respondents like the rodeos, but do not watch television and believe that rodeo is not considered a sport; they also do not question that these activities are considered cultural heritage of their city. Participants believe that with the extinction of rodeos, a decrease in jobs would happen; however, this would not affect the economy of cities. Finally, concerning to the well - being, most of respondent believe that animals suffer during the rodeos and equine species would be the most suitable for these practices.‬ It is suggested that awareness campaigns be carried out to help clarify information related to animal welfare.